ETIKA MUSLIM DI DUNIA VIRTUAL TANTANGAN BARU DALAM RUANG DIGITAL - Nasrullah Nasrullah (Yayasan An-Nur Meunara Baro, 2025)
Digital transformation has fundamentally reshaped the landscape of social interaction and religious expression among Muslims. In this context, the virtual space serves not only as a medium of communication but also as a dynamic arena for constructing new forms of religious identity. This article aims to analyze the ethical challenges and opportunities faced by Muslims in the digital world through a descriptive qualitative approach based on library research. The study focuses on two main dimensions: interpersonal challenges such as the spread of hoaxes, digital backbiting (ghibah), and the ethics of virtual hijab and spiritual challenges, including social media addiction, virtual worship, and digital distraction. Using the framework of maqāṣid al-sharīʿah, the research reveals that many digital behaviors of Muslims are not yet fully aligned with Islamic ethical principles such as tabayyun (verification), amānah (trustworthiness), ḥifẓ al-ʿirdh (protection of dignity), and adab (etiquette). These findings highlight the urgent need to reconstruct a digital ethics rooted in Islamic values to address the complexities of the modern era. Furthermore, this article proposes ethical principles such as digital amar maʿrūf nahi munkar, online social responsibility, and privacy protection as normative foundations for shaping contemporary Muslim digital ethics. In practice, these values can be applied in digital da'wah, virtual communication, and Sharia-compliant online business. This study is expected to enrich contemporary Islamic ethical discourse and contribute to building a digitally literate Muslim society that is socially just, morally grounded, and oriented toward falāḥ (ultimate success).